Crop & pasture science
Crop & pasture science (continuing Australian Journal of Agricultural Research) is an international scientific journal publishing significant outcomes of research into product quality and sustainability of crop and pasture systems. The journal's primary focus is broad-scale cereals, grain legumes, oil seeds, tree crops, and pastures. Papers are encouraged that advance understanding in plant-based agricultural systems through the use of well-defined and original aims, innovative and rigorous experimental design, and strong interpretation. The journal embraces experimental approaches from molecular to whole systems level. The target readership of Crop & Pasture Science is agricultural scientists and plant biologists, industry, administrators, policy-makers, and others with an interest in the challenges and opportunities facing agricultural production. -- Publisher's website [http://www.publish.csiro.au/nid/40/aid/195.htm].